Implementation of a Phase-Sensitive Detector with Cordic Algorithm in Microcontrollers for Low-Cost Eit Demodulation Procedure - Sepulveda-Palma, F (Springer Science and Business Media Deutschland GmbH, 2022)
Electrical impedance tomography is being widely applied to multiphase flow investigation in techniques such as void fraction and dispersed phase flow velocity measurements. The technique is desirable since it presents no ionizing radiation, has a high time resolution, and is relatively low cost. The system works by injecting bidirectional electrical currents into the domain. It is necessary to measure effectively the outcome of the injection, which is commonly a sinusoidal excitation. It is crucial to demodulate this voltage effectively to allow a good accuracy and speed of the system. A way to do this demodulation is by applying a digital phase-sensitive detector, which can divide the signal into amplitude and phase information. It is necessary to multiply a sine and cosine reference to retrieve the signal information, using the Coordinate Rotation Digital Computer (CORDIC) algorithm in this work, to the digitized signal. For that matter, the objective is to implement a digital demodulation procedure utilizing a phase-sensitive detector, generating the reference signals by the CORDIC algorithm using an open-source microcontroller prototyping board, such as the Arduino Due. The accuracy and the noise are investigated further by measuring a reference signal. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.